2015
DOI: 10.1371/journal.pone.0137619
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Interaction with Paracoccidioides brasiliensis Yeast Cells Modulates Fungal Metabolism and Generates a Response to Oxidative Stress

Abstract: Macrophages are key players during Paracoccidioides brasiliensis infection. However, the relative contribution of the fungal response to counteracting macrophage activity remains poorly understood. In this work, we evaluated the P. brasiliensis proteomic response to macrophage internalization. A total of 308 differentially expressed proteins were detected in P. brasiliensis during infection. The positively regulated proteins included those involved in alternative carbon metabolism, such as enzymes involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
83
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 36 publications
1
83
0
1
Order By: Relevance
“…As it concerns the downregulated proteins included those related to glycolysis and protein synthesis. 6 Interestingly, it has been described that most of the Paracoccidioides spp enzymes that participate in both the glycolytic pathway and the tricarboxylic acid (TCA) cycle including glyceraldehyde-3-phosphate dehydrogenase (GADPH), enolase (ENO), fructose-1-6-bisphosphate aldolase (FBA), triose phosphate isomerase (TPI), malate synthase (MLS) and isocitrate lyase (ICL), function as moonlight proteins, this is, they are multifunctional proteins capable of accomplishing different functions often unrelated. 7 Thus, these glycolytic enzymes allow Paracoccidioides spp binding to extracellular matrix (ECM) proteins such as laminin, fibronectin, fibrinogen, type I and IV collagens and plasminogen, among others.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…As it concerns the downregulated proteins included those related to glycolysis and protein synthesis. 6 Interestingly, it has been described that most of the Paracoccidioides spp enzymes that participate in both the glycolytic pathway and the tricarboxylic acid (TCA) cycle including glyceraldehyde-3-phosphate dehydrogenase (GADPH), enolase (ENO), fructose-1-6-bisphosphate aldolase (FBA), triose phosphate isomerase (TPI), malate synthase (MLS) and isocitrate lyase (ICL), function as moonlight proteins, this is, they are multifunctional proteins capable of accomplishing different functions often unrelated. 7 Thus, these glycolytic enzymes allow Paracoccidioides spp binding to extracellular matrix (ECM) proteins such as laminin, fibronectin, fibrinogen, type I and IV collagens and plasminogen, among others.…”
mentioning
confidence: 99%
“…8 These oxidative and nitrosative molecules act on fungal cells through the inactivation of proteins, lipids and cellular enzymes inhibiting respiration, and damaging the DNA and membranes thus leading to the fungal death. 6,9 Therefore, several reports have been shown that Paracoccidioides spp has a powerful antioxidant defense system that allows this fungal pathogen to survive ROS and RNS production; this system includes expression/production of several enzymes such as catalases (CATs), superoxide dismutases (SODs), alternative oxidase (AOX), cytochrome c peroxidase (CCP) and thioredoxins (THX).…”
mentioning
confidence: 99%
See 3 more Smart Citations